Communist Party Penalties in the Soviet Lithuania (1940s–1960s): between Clientelism and Collectivism - Ėmužis , Marius (Genocidas ir rezistencija, 2015)
One of the disciplinary sanctions of the Communist Party in the Soviet Union was party penalties. They were relatively effective and members of the Communist Party were afraid of them. However, many facts show that with the help of “carers” and “patrons” penalties could have been avoided or their effects could have been mitigated. If a penalty could not be avoided (as was often the case in the Stalinist period), with the support and mediation of the party leadership, it was possible relatively quickly to annul the penalty. A number of cases in the period after WWII attest to this. These cases could be treated as a balance between clientelism and the collectivism of Lithuanian representatives of the nomenklatura (administrative personnel), with clientelism dominating the equation. We cannot speak about mutual cover up determined by collectivism due to the lack of any system: after all totally different penalties were applied for similar or even the same “sins”. For example, Vytautas Vazalinskas, a specialist in agriculture, was never punished for being a member of the Riflemen’s Union in the interwar period, while Alfonsas Dirsė, Minister of Health of the Lithuanian SSR , was for this reason removed from office. In many cases penalties could be avoided or mitigated with the help of personal connections and sympathies, i.e. clientelistic services were provided. For example, even the first secretary of the Lithuanian Communist Party Antanas Sniečkus wrote letters to Moscow defending the wrongdoers. Thus clientelism as an element of mutual assistance determined by personal relations in order to avoid or mitigate a party penalty was the most important. A simple withdrawal of a penalty as a disciplinary element of the Communist Party can be identified provided there are no justifying letters, repeat inspections or other actions that show interest of party structures and their leaders. Personal relations helped solve issues considered as discrediting material. Lithuanian Communists understood the situation and did not treat each party member as an enemy if biographies of the family members of that person were “smeared”; this was collectivism determined by the nationality. To mitigate penalties for other types of misdemeanour, e.g. financial misconduct, was more difficult.